Certainty of genuine treatment increases drug responses among intellectually disabled patients. (16th May 2017) - Jensen, Karin B.; Kirsch, Irving; Pontén, Moa; Rosén, Annelie; Yang, Kathy; Gollub, Randy L.; des Portes, Vincent; Kaptchuk, Ted J.; Curie, Aurore
Abstract : Objective: To determine the placebo component of treatment responses in patients with intellectual disability (ID). Methods: A statistical meta-analysis comparing bias-corrected effect sizes (Hedges g ) of drug responses in open-label vs placebo-controlled clinical trials was performed, as these trial types represent different certainty of receiving genuine treatment (100% vs 50%). Studies in fragile X, Down, Prader-Willi, and Williams syndrome published before June 2015 were considered. Results: Seventeen open-label trials (n = 261, 65% male; mean age 23.6 years; mean trial duration 38 weeks) and 22 placebo-controlled trials (n = 721, 62% male; mean age 17.1 years; mean trial duration 35 weeks) were included. The overall effect size from pre to post treatment in open-label studies was g = 0.602 ( p = 0.001). The effect of trial type was statistically significant ( p = 0.001), and revealed higher effect sizes in studies with 100% likelihood of getting active drug, compared to both the drug and placebo arm of placebo-controlled trials. We thus provide evidence for genuine placebo effects, not explainable by natural history or regression toward the mean, among patients with ID. Conclusions: Our data suggest that clinical trials in patients with severe cognitive deficits are influenced by the certainty of receiving genuine medication, and open-label design should thus not be used to evaluate the effect of pharmacologic treatments in ID, as the results will be biased by an enhanced placebo component.